Chemoprofiling of Cucumis pubescens Willd. fruits - Kavitha, R.; Sundari, T.; Srinivasan, P. (Journal of Phytology, 2024)
Cucumis pubescens, a notable therapeutic plant belonging to the Cucurbitaceae family is extensively utilized in South India’s habitual medicine. Despite its medicinal importance, the phytochemical content of this plant remains largely unexplored. The objective of the present study was to examine the phytochemical composition of the fruits of C. pubescens. Initially, HPLC analysis was employed to separate secondary metabolites, revealing seven major phytochemical fractions. The use of a suitable mobile phase system (Acetic acid: Acetonitrile: Water, 4:2:10) at 280 nm facilitated clear isolation. Subsequent spectral analyses confirmed the presence of bioactive compounds. UV-Vis spectral analysis indicated the abundance of flavonoids and tannins. The presence of functional groups, for instance, C=O (carbonyl), C-C (benzene), and Ar-C-H (aromatic hydrocarbon) were validated through FTIR. Further analysis through GC-MS identified 23 bioactive compounds, with quercetin and kaempferol being the predominant ones, followed by gallic acid and caffeic acid. The pharmacological activity of these compounds underscores the therapeutic potential of C. pubescens. In conclusion, this study highlights the rich chemical diversity of C. pubescens, suggesting its potential as a valuable medicinal species with pharmaceutical significance.